Body Posture Analysis Using Rapid Entire Body Assessment (REBA) Method with Skeletal Muscle Complaints in Furniture Workers in Gorontalo Regency - Herlina Jusuf; Nikmatisni Arsad; Putri Ayuningtias Mahdang (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Manual Material Handling (MMH) is an activity that carries the risk of causing muscoskeletal problems in workers. The results of interviews with workers at Faninda Jaya Meubel, they do their work manually, so many experience musculoskeletal complaints due to improper work posture. The aim of this research is to analyze the relationship between body posture and musculoskeletal complaints in Faninda Jaya Meubel workers. The methods used in this research are Rapid Entire Body Assessment (REBA) and Nordic Body Map (NBM). The population in this study was all workers who worked at Faninda Jaya Meubel totaling 23 workers and samples were taken using total sampling techniques. Data analysis used the Chi Square test. The research results found that as many as 43.48% of respondents had a body posture with a very high risk level and as many as 60.87% of respondents had MSDs complaints in the severe complaint category. The results of statistical tests using chi-square showed that there was a relationship between body posture and musculoskeletal complaints among Faninda Jaya Meubel workers (p=0.025). Suggestions for companies to provide facilities for workers such as ergonomic work equipment and machines for working so as to minimize occupational risks.